2010
DOI: 10.3168/jds.2010-3099
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Genetic relationship between calving traits and body condition score before and after calving in Canadian Ayrshire second-parity cows

Abstract: The objective of this study was to investigate the genetic relationship between body condition score (BCS) and calving traits (including calving ease and calf survival) for Ayrshire second-parity cows in Canada. The use of random regression models allowed assessment of the change of genetic correlation from 100 d before calving to 335 d after calving. Therefore, the influence of BCS in the dry period on subsequent calving could be studied. Body condition scores were collected by field staff several times over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Also, Bastin et al, (2010) reported a similar value for BCS heritability (0.13) in Canadian Ayrshires and Holstein cows. Some authors reported higher values for BCS heritability both for dairy cows (Banos et al, 2004;Pryce and Harris, 2006;Zink et al, 2011) and dual purpose cows (Gredler et al, 2006).…”
Section: Descriptive Statisticssupporting
confidence: 50%
“…Also, Bastin et al, (2010) reported a similar value for BCS heritability (0.13) in Canadian Ayrshires and Holstein cows. Some authors reported higher values for BCS heritability both for dairy cows (Banos et al, 2004;Pryce and Harris, 2006;Zink et al, 2011) and dual purpose cows (Gredler et al, 2006).…”
Section: Descriptive Statisticssupporting
confidence: 50%
“…A negative correlation between BCS and DO in first lactation (DO1) of −0.46 was reported by Veerkamp et al (2001), who also reported genetic correlation between BCS and CF of −0.59, which is similar to our result (−0.45). Bastin et al (2010b) reported that cows with genetically high BCS across lactations would have a greater chance of calf survival. Our results suggest that it would be optimal to have a cow with relatively high BCS.…”
Section: Relationships Between Bcs and Fertility Traitsmentioning
confidence: 99%
“…Body condition score reflects the degree of apparent adiposity of the cow and it can be used as an indicator of overall energy status; changes in BCS reflect mobilization of adipose tissue stores during lactation (Roche et al, 2009). In addition, BCS is an important management trait in the dairy herd as it can be used as a predictor of the reproduction, health and welfare status of cows (Dal Zotto et al, 2007;Roche et al, 2009;Bastin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%